A Note on the Generalized q-Bernoulli Measures with Weight α. (6th July 2011) - Kim, T.; Lee, S. H.; Dolgy, D. V.; Ryoo, C. S.
Abstract : We discuss a new concept of theq -extension of Bernoulli measure. From those measures, we derive some interesting properties on the generalizedq -Bernoulli numbers with weightα attached toχ .